RECYCLE MATERIAL SEBAGAI MEDIA PEMBANGKIT MEMORI KOLEKTIF PADA BANGUNAN GEDUNG SERBAGUNA JEMA’AT AHMADIYAH INDONESIA - Intan Fitria Wardani; Suparwoko Suparwoko (Universitas Islam Indonesia, 2020)
Memories are memory that will be a reflection of humans in facing challenges in the future. In the process of memory and memory forgetting, architecture becomes a place where collective memory can be knitted, but also plays a role in the process of forgetting. The purpose of this research is to identify whether the use of recycle of old building materials to new buildings can evoke the collective memory of the Ahmadiyya Community of Indonesia. The old building in this study is the Arif Rahman Hakim building which will be demolished soon. The dismantled material that has been selected will be used in the new building which is currently still in the form of the Ahmadiyya Congregation Versatile Building design. Data collection techniques are by conducting in-depth interviews, documentation and theoretical studies. Analysis technique is done by analyzing the facts obtained and then related to important aspects of the study of theory. The results of this study are that the use of recycle material as a new building element has not been successful in generating collective memory. Because the original shape of the building material has a significant change. The thing that evokes the memory of the users is actually not from the material but from the shape of the space and the atmosphere of the space that is formed.